Peningkatan Kapasitas Kader Posyandu Disabilitas dalam Stimulasi Sensori dan Tumbuh Kembang - Yuni Nurhamida; Sulivan Fitriati; Diana Savitri; Irine Putri Shaliha; Ni’matuzahroh Ni’matuzahroh (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Limited capacity among Posyandu Disabilitas (Integrated Health Post for Persons with Disabilities) cadres in understanding sensory issues and its relation to children's developmental milestones remains a significant challenge in providing appropriate stimulation for children with developmental issues and/or disabilities. This community service program aimed to enhance the knowledge and competencies of Posyandu Disabilitas cadres regarding sensory issues, characteristics, and stimulation strategies to promote optimal child development and support the delivery of holistic services for children attending Posyandu Disabilitas. The program employed a psychoeducational approach consisting of interactive educational sessions and hands-on practical activities. A total of 21 Posyandu Disabilitas cadres participated in the program. Program evaluation demonstrated a 4.5% increase in participants' knowledge following the intervention. These findings indicate that psychoeducation on sensory issues and developmental milestones can effectively improve the knowledge of Posyandu Disabilitas cadres, thereby strengthening their capacity to support children with developmental delays and/or disabilities through appropriate sensory-based stimulation. Nevertheless, several limitations were identified, highlighting the need for continued capacity-building initiatives and sustainable follow-up programs to maximize long-term impact.